Bus Voltage Stabilization Control of Photovoltaic DC Microgrid Based on Fuzzy-PI Dual-Mode Controller - Yu Zhang; Shuhao Wei; Jin Wang; Lieping Zhang (Journal of Electrical and Computer Engineering)
The photovoltaic DC microgrid has strong nonlinearity and time variation. Therefore, traditional dual closed-loop control strategy of voltage and current based on PI controller cannot effectively restrain the fluctuation and impact of DC bus voltage when the dynamic response of the system is improved. Under this situation, in this paper, the fuzzy-PI dual-mode controller is designed to upgrade the traditional dual closed-loop control, taking voltage outer ring into consideration, which is adopted to achieve good transient performance while the bus voltage deviation is large. While the bus voltage deviation is small, the PI controller is utilized for good steady-state performance. Hence, simulation and experimental results show that the fuzzy-PI dual-mode controller has the same advantages with both fuzzy control and PI control; in other words, it has the features of speedy response, low overshoot, good robustness, and strong anti-interference under different working conditions.